THE STUDY OF BIOFLOC EFFECTIVENESS AS FEED ON TILAPIA (Oreochromis niloticus) AND SANGKURIANG CATFISH (Clarias gariepinus) - Ahadiftita Hafsha K; Supono Supono; Limin Santoso (Jurusan Perikanan dan Kelautan, 2016)
Biofloc system is a technology in aquaculture which utilized waste mainly in form of anorganic nitrogen. The anorganic nitrogen will be converted into protein in the form of bacterial biomass by heterotrophic bacteria. The growth of heterotrophic bacteria is stimulated by the addition of a carbon source. This research aimed were to study the absolute growth, daily growth rate, specific growth rate and survival rate of tilapia and sangkuriang catfish which fed on biofloc. The research used Completely Randomized Design (CRD) which consisted of two treatments and four replication. The study lasted for 40 days, with the frequency of feeding biofloc was three times a day ie morning, afternoon and evening. Growth sampling was done every 10 days, observation of water quality every 8 days, and ammonia test was done at the beginning, middle and end of research. The results showed that tilapia which fed on biofloc have absolute growth, daily growth rate, specific growth rate, and survival rate better than those of sangkuriang catfish.